THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON AUDIT QUALITY - Oktarina, Dian; Delisa Damanik, Nella (Ecopreneur.12, 2024)
This study examines the effect of auditor ethics, auditor accountability, due professional care, and audit fees on audit quality in public accounting offices in Surabaya. This study uses 100 data from respondents who are external auditors working at a public accounting office in Surabaya. This research includes quantitative research with primary data types. Data collection using a questionnaire with a Likert scale. Data analysis was performed using multiple linear regression method with Smart-PLS software. The results of this study indicate that auditor ethics does not affect audit quality. Meanwhile, auditor accountability, due professional care, and audit fees significantly affect audit quality.